Domestication and Formulation of Rhizopodopsis Javensis as Tempeh Starter - GAYUH RAHAYU; EFRIWATI EFRIWATI; SEPTINA VERONICA (Microbiology Indonesia, 2021)
ABSTRACT Domestication of wild fungal strains involved in the manufacture of traditional fermented foods often occurs spontaneously. Rhizopodopsis javensis (Rh. javensis) is taxonomically close to Rhizopus. The wild strain Rhizopodopsis javensis has found in cool climates can be developed as a starter in tempeh production in temperate regions. Before formulating it as a tempeh starter, a wild strain of Rh. javensis needs to be domesticated in human-made niches. A wild strain of Rh. javensis was domesticated by subculture using rice flour media at optimum growth temperature and carried out every five days. The spore's density and viability and the starter's water content were used to determine its quality. The results showed that Rh. javensis grew optimally at 22 â„ƒ. With seven-time subcultures using rice flour media, the domestication process did not change the Rh. javensis growth rate and colony appearance. The growth rate of Rh. javensis is relatively the same as that of commercial tempeh starter and pure R. microsporus var. oligosporus, at each optimal growth temperature. In the rice flour media as a carrier, Rh. javensis produces spore's density that is relatively the same as that of commercial tempeh starter but with lower spore's viability and higher water content. Therefore, Rh. javensis cannot be used as a starter to produce tempeh in the temperate region. The carrier material and drying processes still need to be modified to increase spore viability and improve the overall quality, including the starter's lifespan. Keywords: food fermentation, Rhizopus microsporus var. oligosporus, spore's viability, starter quality, wild strain ABSTRAK Domestikasi galur liar kapang yang terlibat dalam dalam pembuatan makanan fermentasi tradisional, sering terjadi secara spontan. Rhizopodopsis javensis (Rh. javensis) merupakan salah satu galur liar kapang yang memiliki hubungan taksonomi dekat dengan Rhizopus. Strain liar ini ditemukan di daerah beriklim sejuk, sehingga berpotensi untuk dikembangkan sebagai starter tempe untuk produksi di daerah beriklim sedang. Untuk mendapatkan kultur yang tumbuh subur di relung (niches) buatan manusia, strain liar Rh. javensis perlu didomestikasi terlebih dahulu. Penelitian ini bertujuan untuk mendomestikasi strain Rh. javensis liar yang dilanjutkan dengan memformulasikannya sebagai starter tempe. Domestikasi dilakukan dengan menumbuhkan strain liar Rh. javensis pada media tepung beras pada suhu pertumbuhan optimum dan diulangi setiap lima hari. Kerapatan dan viabilitas spora, serta kadar air starter digunakan sebagai penilaian keberhasilan starter. Hasil penelitian menemukan Rh. javensis tumbuh optimal pada suhu 22 â„ƒ. Domestikasi dengan cara subkultur koloni Rh. javensis pada media tepung beras selama 7 kali tidak mengubah kecepatan pertumbuhan Rh. javensis dan penampakan koloni. Laju pertumbuhan Rh. javensis relatif sama dengan laju pertumbuhan starter tempe komersial dan R. microsporus var. oligosporus murni, pada suhu optimum pertumbuhan masing-masing. Formulasi tepung beras sebagai media pembawa starter Rh. javensis, menghasilkan kerapatan spora yang relatif sama dengan starter tempe komersial, namun viabilitas sporanya rendah dan kadar airnya tinggi. Starter Rh. javensis belum dapat digunakan untuk membuat tempe. Substrat dan proses pengeringan masih perlu dimodifikasi untuk meningkatkan viabilitas spora dan kualitas starter tempe secara keseluruhan, termasuk umur simpan starter. Keywords: fermentasi makanan, kualitas starter, Rhizopus microsporus var. oligosporus, strain liar, viabilitas spora